The Effect of PBL Hybrid Learning on the Higher Order Thinking Skills of Seventh Grade Students in Global Warming and Their Environmental Care Attitudes - Sio Tuti Gultom; Parsaoran Siahaan; Andi Suhandi (Jurnal Penelitian Pendidikan IPA, 2021)
This study aimed to investigate the effect of problem-based learning (PBL) hybrid learning on the higher order thinking skills (HOTS) of seventh grade students in global warming and their environmental care attitudes. The study was conducted using a quasi- experimental design. The participants of the study were 68 students, divided into two groups: one an experimental group (n=34) and the other a control group (n=34). HOTS test (15 multiple choices) and questionnaire (hands on activity) were designed to confirm the study’s validity and reliability. SPSS was used to analyze the data. The finding revealed that there were statistically significant differences between the experimental and the control group. The results of post-test data processing (One-Way ANOVA with =0.05) show that H0 is rejected and Ha is accepted. This shows that there is a significant effect of PBL hybrid learning on the higher order thinking skills of seventh grade students in global warming and their environmental care attitudes. The study is recommended to use in Indonesia’s education system after covid-19 pandemic end to increase education quality. This study showed increasing student’s environmental care awareness attitudes